2014
DOI: 10.2214/ajr.13.12093
|View full text |Cite
|
Sign up to set email alerts
|

Value of Gadolinium-Enhanced MRI in Detection of Acute Appendicitis in Children and Adolescents

Abstract: Gadolinium-enhanced images and T2-weighted images are most helpful in the assessment of acute appendicitis in the pediatric population. These findings have led to protocol modifications that have reduced imaging time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
36
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(37 citation statements)
references
References 23 publications
1
36
0
Order By: Relevance
“…With the diagnostic boundary set at ≥ 7mm, Rosines et al 30 and Herliczek et al 26 reported sensitivities of 94% 30 and 100% 26 and specificities of 100% 30 , 96% 26 respectively. It can be therefore be inferred that the 1mm difference in appendiceal outer diameter measurement made very little difference to reported sensitivity and specificity values and as such, the smaller value (≥ 6mm) is recommended to reduce risk of false negative findings.…”
Section: Discussionmentioning
confidence: 99%
“…With the diagnostic boundary set at ≥ 7mm, Rosines et al 30 and Herliczek et al 26 reported sensitivities of 94% 30 and 100% 26 and specificities of 100% 30 , 96% 26 respectively. It can be therefore be inferred that the 1mm difference in appendiceal outer diameter measurement made very little difference to reported sensitivity and specificity values and as such, the smaller value (≥ 6mm) is recommended to reduce risk of false negative findings.…”
Section: Discussionmentioning
confidence: 99%
“…The number of patients included in these studies ranged from 38–510 and the mean age ranged from 7–14.4 years. In three studies, patients who showed inconclusive results on US examination prior to MRI were included . Patients who underwent MRI were selected and included in this meta‐analysis from studies by Kearl et al (192 out of 583 patients) .…”
Section: Resultsmentioning
confidence: 99%
“…In terms of the reference standard domain, there was generally an unclear risk of bias because the blinding procedure used for the pathologist who determined the final diagnosis was not mentioned in any of the studies. Regarding the flow and timing domain, six studies had an unclear risk of bias because the clinical follow‐up period in cases of negative MRI findings was not mentioned …”
Section: Resultsmentioning
confidence: 99%
“…A study conducted by Rosines et al [18] reported that contrast-enhanced images are helpful for the assessment of acute appendicitis in the pediatric population. However, those authors did not include DWI in their MRI protocol, which has proven valuable in other abdominal and bowel diseases [19].…”
Section: Discussionmentioning
confidence: 99%